2011
DOI: 10.3171/2011.1.focus10308
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of improved surgical outcome following endoscopy for nonfunctioning pituitary adenoma removal

Abstract: Object Because of their size and lateral extension, total removal of nonfunctioning pituitary adenomas (NFPAs) remains a challenge and postoperative tumor remnants are frequent. Endoscopy has improved the surgeon's view; however, its superiority in terms of surgical outcome remains undetermined. The authors' aim in this study was to compare the clinical results and morbidity between microscopic and endoscopic techniques in 164 patients with NFPAs. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 42 publications
9
86
0
Order By: Relevance
“…Nowadays, this approach is becoming the first-line technique and most of pituitary surgeons are shifting to the endoscopic technique because of the excellent visualization of supra and para-sellar compartments it provides and a painless shorter postoperative course. Despite the absence of randomized studies proving definitely the superiority of endoscopic surgery upon microsurgery, the recent literature is accumulating evidence in favor of endoscopy especially for non-functioning pituitary adenomas (Dehdashti et al, 2008;Kassis et al 2009 ;Frank et al, 2006, Higgins et al, 2008Messerer et al, 2011;Schaberg et al, 2010). The rate of gross total removal is definitely higher in endoscopic series than in microscopic ones, for such adenomas.…”
Section: Endoscopic Endonasal Pituitary Surgerymentioning
confidence: 98%
See 2 more Smart Citations
“…Nowadays, this approach is becoming the first-line technique and most of pituitary surgeons are shifting to the endoscopic technique because of the excellent visualization of supra and para-sellar compartments it provides and a painless shorter postoperative course. Despite the absence of randomized studies proving definitely the superiority of endoscopic surgery upon microsurgery, the recent literature is accumulating evidence in favor of endoscopy especially for non-functioning pituitary adenomas (Dehdashti et al, 2008;Kassis et al 2009 ;Frank et al, 2006, Higgins et al, 2008Messerer et al, 2011;Schaberg et al, 2010). The rate of gross total removal is definitely higher in endoscopic series than in microscopic ones, for such adenomas.…”
Section: Endoscopic Endonasal Pituitary Surgerymentioning
confidence: 98%
“…Postoperative anterior pituitary dysfunction may occur in 13% to one third of patients with pituitary adenomas managed endoscopically, depending of the preoperative condition (Messerer et al, 2011). Endocrine results are clearly poorer for craniopharyngiomas while unclear or sparse for the other sellar tumors.…”
Section: Endocrinological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensenat et al [ 34 ] and Messerer et al [ 102 ] compared patients with non-functional pituitary adenomas who underwent TS tumor resection with either an endonasal endoscopic or purely microscopic approach. Both studies demonstrated a significantly higher rate of gross total resection in the endoscopic group (60% vs. 35% and 74% vs. 50%, respectively).…”
Section: Pituitary Adenomasmentioning
confidence: 99%
“…Surgical resection represents the mainstay of treatment, and this is typically via an endoscopic endonasal approach (5). However, complete resection may be challenging due to the firm consistency and highly vascularised nature of these tumours.…”
Section: Introductionmentioning
confidence: 99%